2005
DOI: 10.1158/1055-9965.epi-05-0003
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Calcium Supplementation and Nonsteroidal Anti-inflammatory Drugs and the Risk of Colorectal Adenomas

Abstract: Background: Calcium and aspirin have both been found to be chemopreventive against colorectal neoplasia. However, the joint effect of the two agents has not been well investigated. Methods: To explore the separate and joint effects of calcium and aspirin/nonsteroidal anti-inflammatory drugs (NSAID), we used data from two large randomized clinical trials among patients with a recent history of colorectal adenomas. In the Calcium Polyp Prevention Study, 930 eligible subjects were randomized to receive placebo or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 61 publications
2
16
1
Order By: Relevance
“…Our results were consistent with one study 38 but in direct contrast to another, 39 where the association of dietary calcium was limited to patients not taking NSAIDs. However, that study did find supplemental calcium to be more strongly associated with risk of adenomas in those taking NSAIDs at least once a week.…”
Section: Discussionsupporting
confidence: 93%
“…Our results were consistent with one study 38 but in direct contrast to another, 39 where the association of dietary calcium was limited to patients not taking NSAIDs. However, that study did find supplemental calcium to be more strongly associated with risk of adenomas in those taking NSAIDs at least once a week.…”
Section: Discussionsupporting
confidence: 93%
“…Simulated outcomes are based on each of the 4 interventions which include (i) colonoscopy alone, (ii) colonoscopy with aspirin, (iii) colonoscopy with calcium, and (iv) colonoscopy, aspirin, and calcium chemoprevention. All inputs for effectiveness of the different strategies have been determined from previous RCTs of the use of these agents for chemoprevention of CRC (15)(16)(17). Each of these interventions is compared with a baseline scenario where no screening intervention is used.…”
Section: General Assumptions Of the Markov Processmentioning
confidence: 99%
“…The prevalence of any adenoma at initial colonoscopy at age 50 was 36.6 years (21), with 27.0% for low-grade polyps (21), 9.6% for a high-grade polyp (21), and 1.0% for CRCs (21). The adenoma development rate per year is 17.1% with no chemoprevention (7), and the metachronous adenoma rate was set at 10.4% for aspirin, 13.7% for calcium, and 6.8% for aspirin plus calcium chemoprevention, based upon rates of adenoma prevention from RCTs (15)(16)(17). The Markov model used the metachronous rate to determine the number of polypectomies and surveillance colonoscopies.…”
Section: Transition Probabilitiesmentioning
confidence: 99%
“…If one translates these data into numbers of adenomas that would be reduced in the United States by increased calcium intake this would total approximately 26 000 cases of adenomas with a more important impact on the advanced lesions. Subsequent analyses by Baron's group showed that most of the effect of calcium in lowering the incidence of recurrent adenomas occurred in individuals who had baseline levels of serum 25 hydroxy vitamin D above the median (about 29 ng per mL) with little effect in individuals with lower levels [10] . These data strongly suggest that it is the combination of calcium and vitamin D which is important in altering adenoma recurrence.…”
Section: Calciummentioning
confidence: 99%